Pyridinium-catalyzed decarboxylative borylation of benzoyl peroxides - Shuxian Zhu; Jianxiang Yan; Yao Zhou; Kai Yang; Qiuling Song (Green Synthesis and Catalysis, 2021)
A pyridinium salt catalyzed radical borylation of benzoyl peroxides is reported herein. A range of benzoyl peroxides having different electronic properties were well compatible in this borylation reaction, delivering various arylboronates in good yields at ambient temperature. The current method features simple operation, additive- and base-free, transition-metal-free and mild conditions.